Sharia economy as a model for Palestinian development: An international political economy perspective - Fawaz Muhammad Khaer (PRIVIETLAB, 2025)
This study investigates the pursuit of economic self-determination in Palestine by advocating economic principles that adhere to Shariah principles. This analysis critically examines the importance of economic sovereignty and the potential consequences of global political dynamics for Palestine's economic development. This research highlights the critical role played by a wide range of international stakeholders, including financial institutions, governmental entities, and non-governmental organizations (NGOs), in supporting Palestine’s economic progress. Moreover, this emphasizes the critical nature of addressing the fundamental shortcomings of the Palestinian economy and cultivating sustainable economic growth. Furthermore, this study examines the capacity of economic methodologies that adhere to Sharia principles to aid in attaining Palestinian economic self-determination. It explicitly emphasizes principles, including ecological sustainability, societal accountability, and fairness.